2016
DOI: 10.1007/s00784-016-1831-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 1% ropivacaine for postoperative analgesia after lower third molar surgery: a prospective, randomized, double-blinded clinical study

Abstract: Since pain control related to third molar surgery requires the effective surgical anesthesia and postoperative analgesia, the use of 1 % ropivacaine could be clinically relevant in a selection of appropriate pain control regimen for both surgical procedure and early postsurgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Statistically, our study is different from those by Pellicer-Chover et al [ 39 ] and Brković et al [ 5 ], which found no clear statistically significant differences in postoperative pain after the extraction of wisdom teeth using different types of anaesthetics. In our study, the patients who received only the articaine block reported initial pain immediately after the anaesthetic wore off, while those with bupivacaine reported it later.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Statistically, our study is different from those by Pellicer-Chover et al [ 39 ] and Brković et al [ 5 ], which found no clear statistically significant differences in postoperative pain after the extraction of wisdom teeth using different types of anaesthetics. In our study, the patients who received only the articaine block reported initial pain immediately after the anaesthetic wore off, while those with bupivacaine reported it later.…”
Section: Discussioncontrasting
confidence: 99%
“…This is due to higher osmotic pressure in the capillaries (Starling’s law), which produces the most common postoperative consequences, such as pain, trismus, and swelling, all of which are related to the local inflammatory reaction that occurs, in which cyclooxygenase (COX) and prostaglandins play a crucial role. For this reason, there can be serious postoperative discomfort even when the surgical extraction necessitates a simple technique [ 5 ]. The literature has described how these complications are influenced by various factors, including the difficulty of the procedure, the age and gender of the patient, and the surgeon’s experience [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedersen administered dexamethasone in the masseter muscle before the start of the operation of third molar surgery for the purpose of pain reduction [38]. Preoperatively administering 2 mL 1% ropivacaine in the pterygomandibular space for IANB anesthesia during third molar surgery and 2 mL 2% lidocaine with epinephrine 1:80.000 as a primary local anesthetic, with an additional injection of 2 mL 1% ropivacaine in the pterygomandibular space postoperatively, for the purpose of controlling the postoperative pain, showed that ropivacaine achieved greater pain reduction than lidocaine/epinephrine did and increased the duration of postoperative analgesia, whether ropivacaine was the primary or supplemental local anesthetic [77]. The suggested method of "twin-mix" mixture prepared by directly mixing 1.8 mL of 2% lignocaine with 1:200,000 epinephrine and 1 mL/4 mg dexamethasone in the syringe and administering it in the pterygomandibular space for IANB anesthesia showed similar clinical effects on the postoperative quality of life as a conventional method of injecting steroids into the intraoral-submucosal, intramuscular, intravenous and per-oral routes [78].…”
Section: Discussionmentioning
confidence: 99%
“…After its commercial release, ropivacaine has been extensively used for perioperative pain relief in the medical field, with consistently better outcomes than other local anesthetic agents [ 4 ]. Its use in the dental discipline has expanded to studies on periodontic procedures to evaluate its anesthetic efficacy [ 11 ], topical anesthesia of the oral mucosa [ 12 ], simple extraction procedures [ 3 13 14 ], lower third molar surgeries[ 1 4 5 15 16 17 18 19 ], surgical removal of the upper third molars[ 20 ], surgical removal of chronic periapical lesions [ 21 ], oral aphthosis [ 22 ], mandibular osteotomy [ 23 ], and postoperative pain control after elective cleft palate repair in children [ 24 ].…”
Section: Discussionmentioning
confidence: 99%